Code-Switching as a Pedagogical Strategy in Arabic Language Teaching at the State Islamic University - Siregar, Syahri Ramadhan; Syukur, Hasan; Asror, M. Khozinul; Putra, Muhamad Fatih Budiman; Jalal, Darul; Siregar, Ahmad Mukhlis (Study Program of Arabic Language Teaching, 2026)
The increasing use of multiple languages in educational settings has intensified code-switching, particularly in foreign language classrooms. This study aims to investigate (1) the reasons why Arabic language students engage in code-switching and (2) the extent to which code-switching supports Arabic language teaching from teachers’ perspectives. This research employed a mixed-methods design. The population consisted of Arabic language students and lecturers from three Indonesian universities: UIN Maulana Malik Ibrahim Malang, UIN Sunan Ampel Surabaya, and UIN Sunan Kalijaga Yogyakarta. Using purposive sampling, 300 students were selected as respondents for the quantitative phase, and 9 lecturers were selected for the qualitative phase. Quantitative data were collected through a 21-item Likert-scale questionnaire and analyzed using the Statistical Package for the Social Sciences (SPSS). Qualitative data were obtained through semi-structured interviews and analyzed using the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The findings reveal that the primary reasons for code-switching are academic, particularly to ask questions, clarify meaning, and compensate for limited vocabulary, while social and personal factors are less significant. From the teachers’ perspectives, code-switching provides pedagogical benefits, such as enhancing students’ comprehension of complex concepts and unfamiliar vocabulary. However, it also presents drawbacks, including reduced exposure to the target language and limited vocabulary development. This study concludes that code-switching functions as a strategic pedagogical tool when used selectively, especially at lower proficiency levels, but should be minimized to optimize Arabic language acquisition.